Japanese and Chinese infrastructure development strategies in Central Asia. (16th July 2018) - Dadabaev, Timur
Abstract: This paper compares Japanese and Chinese infrastructure development strategies in post-Soviet Central Asia (CA) by analyzing the similarities and differences in the approaches of the two Asian economic powers. This paper develops several arguments with respect to the Japanese and Chinese approaches to infrastructure development in CA. This paper argues that the discourse of mutually exclusive interests in China and Japan's development of various infrastructure-related projects in CA is empirically unproven. Most of the Chinese engagements emphasize the creation of energy and transportation infrastructure (construction), while Japan's main areas of focus are the maintenance, modernization, and rehabilitation of current infrastructure. Thus, this paper suggests that China positions itself as CA's leading economic partner, while Japan is CA's leading assistance provider. These two roles have different implications. Furthermore, the current infrastructure engagements of Japan (from assistance to partnership) and China (from exploitation to contribution to the region) in CA demonstrate both countries' attempts to adjust and search for new opportunities.